The skin microbiome in psoriatic arthritis: methodology development and pilot data. (26th February 2015) - Castelino, Madhura; Eyre, Stephen; Moat, John; Fox, Graeme; Martin, Paul; Ijaz, Umer; Quince, Christopher; Ho, Pauline; Upton, Mathew; Barton, Anne
Abstract: Background: Skin microbiota are likely to be important in the development of conditions such as psoriatic arthritis. Profiling the bacterial community in the psosriatic plaques will contribute to our understanding of the role of the skin microbiome in these conditions. The aim of this work was to determine the optimum study design for work on the skin microbiome with use of the MiSeq platform. The objectives were to compare data generated from two platforms for two primer pairs in a low density mock bacterial community. Methods: DNA was obtained from two low density mock communities of 11 diverse bacterial strains (with and without human DNA supplementation) and from swabs taken from the skin of four healthy volunteers. The DNA was amplified with primer pairs covering hypervariable regions of the 16S rRNA gene: primers 63F and 519R (V1-V3), and 347F and 803R (V3-V4). The resultant libraries were indexed for the MiSeq and Roche454 platforms and sequenced. Both datasets were de-noised, cleaned of chimeras, and analysed by use of QIIME software (version 1.8.0). Findings: No significant difference in the diversity indices at the phylum and the genus level between the platforms was seen. Comparison of the diversity indices for the mock community data for the two primer pairs demonstrated that the V3-V4 hypervariable region had significantly better capture of bacterial diversity than did the V1-V3 region. Amplification with the same primer pairs showed strong concordance within each platform (98·9–99·8%), with negligible effect of spiked human DNA contamination. Comparison at the family level classification between samples processed on the MiSeq and Roche454 platforms using the V3-V4 hypervariable region also showed a high level of concordance (87%), although less so for the V1-V3 primers (10%). The pilot data from healthy volunteers were similar. Interpretation: Results obtained from the V3-V4 16S rRNA hypervariable region, sequencing on the MiSeq and Roche454 platforms, were concordant between replicates, and between each other. These findings suggest that the MiSeq platform, and these primers, is a comparable method for determining skin microbiota to the widely used Roche454 methodology. Funding: NIHR Manchester Musculoskeletal Biomedical Research Unit.